Ownership Claim Pursuant to Resolution No. 1198 upon the Mere Opening of the Property Statement - Al-Qassab, Fatimah Majid Mohammed (Journal of Cultural Analysis and Social Change, 2026)
This study examines the ownership claim established pursuant to Iraqi Revolutionary Command Council Resolution No. (1198) of 1977 based solely on the procedure of opening the property statement, without the existence of a written external sale contract. Following the enactment of the Iraqi Civil Code and the imposition of formal registration as a prerequisite for the transfer of real property ownership, numerous practical disputes emerged due to reliance on informal sale arrangements. Resolution No. (1198) introduced an exceptional mechanism recognizing an undertaking to transfer ownership when the beneficiary occupies the property or constructs buildings thereon. The research addresses a significant procedural and judicial dilemma arising when the parties merely initiate the statement-opening procedure before the Real Estate Registration Directorate, after which the seller retracts or refuses to complete the registration. The central issue concerns whether opening the statement constitutes a valid undertaking sufficient to establish an ownership claim under the Resolution, or whether such claims must be dismissed for lack of a formal or external contractual document. Adopting an analytical and applied methodology, the study analyzes relevant legal texts, procedural rules, and divergent judicial rulings issued by Iraqi Courts of Appeal acting in their cassation capacity. It highlights the inconsistent judicial approaches regarding reliance on the statement-opening procedure and underscores the decisive role of judicial discretion in resolving ownership disputes. The study concludes with practical findings and recommendations aimed at achieving judicial consistency and enhancing legal protection for good-faith purchasers.